ST-Drop: Uma Nova Estratégia de Gerenciamento de Buffer em Redes Oportunistas D2D - Silva, Michael D.; Nunes, Ivan O.; Mini, Raquel A. F.; Loureiro, Antonio A. F. (Anais do Simpósio Brasileiro de Redes de Computadores e Sistemas Distribuídos (SBRC); 2017: Anais do XXXV Simpósio Brasileiro de Redes de Computadores e Sistemas Distribuídos, 2017)
In D2D opportunistic networks, nodes act as relays for transmitting messages to other nodes according to an opportunistic routing algorithm. In this scenario, each node uses a buffer with limited capacity to store these messages temporarily until they are propagated to a neighbor node according to an opportunistic routing protocol. However, when multiple messages are forwarded in the network, the number of incoming messages may exceed the nodes' capacity, causing a buffer overflow. Therefore, message dropping policies are very important to this problem, because when a message is dropped, there is a chance that other copies of this message still exist in the network. This work proposes a new buffer management algorithm for opportunistic routing in D2D networks named ST-Drop (Space-Time-Drop). We evaluate our solution in three different types of opportunistic routing algorithms: epidemic-based, probabilistic, and social-aware. We conduct simulations using two different publicly available data sources and consider different network traffic loads. Compared to other message drop policies, ST-Drop obtained the highest message delivery ratio in all considered scenarios and the lowest overhead when applied to the state-of-art social-aware and probabilistic routing algorithms, namely, Bubble Rap and Prophet.